Concurrence of systemic lupus erythematosus and psoriatic arthritis: literature data and a case report - E. M. Agafonova; N. G. Klyukvina; M. M. Urumova (Современная ревматология)
Systemic lupus erythematosus (SLE) is an autoimmune systemic inflammatory disease with various clinical manifestations. There are descriptions of overlap syndromes when the signs of several systemic connective tissue diseases, such as rheumatoid arthritis, systemic sclerosis, dermatomyositis, and SjЪgren's syndrome, are simultaneously recorded. Psoriasis belongs to chronic skin diseases of multifactorial genesis, which is determined by genetic, immunological, and environmental factors. About one out of three patients with psoriasis develops psoriatic arthritis (PsA), an inflammatory joint injury. The concurrence of SLE and PsA is rare; there are very few reports on such clinical situations. A special variant of SLE, such as subacute cutaneous lupus erythematosus, can mimic skin lesions in psoriasis, which causes diagnostic difficulties.The paper gives the data available in the literature on the concurrence of SLE, PsA, and psoriasis. It discusses the specific features of the differential diagnosis of the concurrence of the two nosological entities and its treatment policy. The authors give their own clinical case of the concurrence of SLE and PSA, as well as several descriptions of such cases available in the literature.